Language and territorialization: Food consumption and the creation of urban Indigenous space - Patrick, Donna; Shaer, Ben; BUDACH, Gabriele (2017)
peer reviewed In this paper we analyze two March 2010 events in Ottawa, Canada involving the preparation and consumption of seal-meat: one an Inuit seal feast, held at a Inuit community center, in which raw seal was carved and eaten in accordance with traditional Inuit practices; the other a “seal lunch”, held in the Parliamentary Dining Room for Members of Parliament, in support of the Canadian seal-hunt. Methodologically, we make use of both participatory action research and detailed textual analysis of media reports, and frame our analysis in terms of moral geographies, social and cultural values associated with food, and meaning-making systems embedded in discourses, which serve to construct and constitute particular power relations. Doing so leads us to claim that the two seal-meal events drew on and conveyed radically different meanings. The Inuit meal, though not overtly political, represented an act of food sovereignty and a claim to Inuit territoriality in the city. The Parliamentary seal lunch, by contrast, had a clear political aim, as a form of protest against the European Union decision to ban seal meat and other products. Yet, while purporting to support Inuit seal-hunting, the Parliamentary meal effectively communicated the utter foreignness of seal meat and Inuit foodways with respect to Western tastes and discourses about food and environmentalism—a fact that emerges through our ethnographic and media analysis of the two seal lunch events. Multilingual literacy practices of urban Inuit